Comparison of Personality Traits in Gifted Students with the Highest and Lowest Levels of Creativity - Tabatabaei Irani, Pardis; Afrooz, Gholam Ali; Sajjadi Anari, Sayed Saeed (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2026)
Objective: The objective of this study was to compare the personality traits of gifted students with high creativity and those with low creativity. Methods and Materials: This applied study employed a causal–comparative design. The statistical population consisted of all gifted secondary school students in the city of Isfahan during the 2022–2023 academic year. From this population, 217 students were selected through simple random sampling based on Cochran’s formula. Data were collected using Abedi’s standardized Torrance Creativity Questionnaire and the Personality Traits Questionnaire developed by Buss and colleagues, which assesses fair-minded, assertive, egalitarian, and introverted personality traits. Questionnaires were administered electronically after obtaining the necessary permissions and informed consent. Descriptive statistics were used to summarize the data, and independent samples t-tests were conducted to examine differences in personality traits between students with high and low creativity. All analyses were performed using SPSS version 27 with a significance level of 0.05. Findings: Inferential analysis revealed statistically significant differences between gifted students with high and low creativity across all personality traits. Students with high creativity scored significantly higher in fair-minded personality, assertive personality, and egalitarian personality. In contrast, students with low creativity demonstrated significantly higher levels of introverted personality. The results of Levene’s tests confirmed the homogeneity of variances, and the t-test results indicated that all observed differences were statistically significant at the 0.05 level or lower. Conclusion: The findings indicate that creativity level among gifted students is associated with distinct personality profiles, suggesting that personality traits play a meaningful role in the expression of creativity. Recognizing these differences can contribute to more effective identification, counseling, and educational interventions aimed at fostering creativity in gifted learners.